CLINICAL CHARACTERISTICS AND ENDOSCOPIC FINDINGS OF SYMPTOMATIC DYSPEPSIA PATIENTS IN RURAL AND URBAN AREAS: A RETROSPECTIVE COMPARATIVE STUDY. - Dash, Kaibalya Ranjan; Dash, Amulya Ranjan (Student's Journal of Health Research Africa, 2024)
Background Dyspepsia is a common gastrointestinal disorder affecting a substantial portion of the global population, characterized by various symptoms such as epigastric pain and early satiety. Understanding the differences in dyspeptic presentations among diverse populations can inform more effective diagnostic and treatment strategies. This study seeks to contrast the clinical characteristics and endoscopic findings of dyspeptic patients from rural and urban areas. Methods This retrospective comparative study was conducted at SCB Medical College & Hospital in Cuttack over one year, involving 100 patients diagnosed with dyspepsia. Participants were selected using non-probability consecutive sampling, with inclusion criteria focused on individuals aged 16 to 75 years presenting with relevant gastrointestinal symptoms. Endoscopic evaluations were performed to assess the underlying conditions. Results The study revealed that the majority of patients were aged 31-40 years (25%), with a slight female predominance (55%). The rapid urease test indicated a 60% positive rate for Helicobacter pylori infection among participants. Notable endoscopic findings included erosive antral gastritis observed in 30 rural patients and 35 urban patients, highlighting the differences in gastrointestinal conditions between populations. Conclusion The findings underscore the need for tailored healthcare interventions based on demographic factors, as urban patients exhibited a higher prevalence of certain dyspeptic symptoms. This study emphasizes the importance of understanding the clinical and endoscopic variations of dyspepsia to enhance patient care. Recommendations Initial endoscopy for new-onset dyspepsia is recommended in patients 50 years of age or older or those with alarm features.